Authentication process enhancements in WiMAX networks - Alezabi, Kamal Ali; Hashim, Fazirulhisyam; Hashim, Shaiful Jahari; Mohd Ali, Borhanuddin; Jamalipour, Abbas (John Wiley & Sons, 2016)
Authentication is one of the most important security processes in Worldwide Interoperability for Microwave Access (WiMAX) networks. This process allows the receiver (whether base station or subscriber station) of a packet to be confi- dent of the identity of the sender and the integrity of the message. Most attacks will attempt to violate the authentication process. If such attacks become successful, an attacker will gain an illegitimate access to network resources, thus increasing the probability of future malicious attacks. A number of algorithms and methods have been proposed to improve the security level of authentication in WiMAX networks. However, the evaluations of these algorithms and methods have always been based on a particular aspect, such as reducing overhead, protecting unauthenticated management messages, preventing WiMAX from external attacks, and protection during the handover process. Motivated by these variations, we review the state of art of WiMAX authentication mechanisms, namely, PKMv1, PKMv2, and the recent authentication protocols. We discuss their mechanisms, strengths, weaknesses, and potential countermeasures against each other. Our discussion is based on four categories, namely, enhancements, differences, advantages, and limitations.